Review of resuscitation physiology in children - Shehadeh,AJ; Soliman,A; Maconochie,I (Paediatrics and Child Health United Kingdom, 2019)
More than one quarter of children survive to hospital discharge after in-hospital cardiac arrests, and 5–10% of children survive to hospital discharge after out-of-hospital cardiac arrests. Cardio-pulmonary resuscitation (CPR)differs in children from adults. Following the Airway, Breathing, Circulation format, this article reviews the physiology of paediatric cardio-pulmonary resuscitation. It addresses the appropriate interventions during CPR, mechanisms of action of commonly used drugs and special resuscitation circumstances: premature and newly born infants, traumatic cardiac arrest, and ECMO (Extracorporeal Membrane Oxygenation). New exciting discoveries in resuscitation science postulate that the key factor in improving outcomes of paediatric cardiac arrest is improving the quality of interventions. A thorough understanding of the physiology underpinning CPR is helpful in ensuring optimal delivery of CPR in children and improving clinical outcomes.